PERSEPSI TERHADAP E-GOVERNMENT PADA PEGAWAI DIREKTORAT JENDERAL PERBENDAHARAAN - Putu Jaya Permana; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
This study aimed to analyze employees of Directorate General of Treasury perception towards e-government that measure the effect of system quality, information quality, perceived usefulness and perceived ease of use towards e-government user acceptance. There were five variables in this research that consist of four independent variables namely system quality, information quality, perceived usefulness and perceived ease of use and one dependent variable namely e-government acceptance. Statistical method used in this research is multiple regressionThe results of this study showed that perceived usefulness and perceived ease of use significantly affect user acceptance of Directorate General of Treasury e-government.